Characteristics of functional ice cream produced with probiotic Saccharomyces boulardii in combination with Lactobacillus rhamnosus GG - Goktas, Hamza; Dikmen, Hilal; Bekiroglu, Hatice; Cebi, Nur; Dertli, Enes; Sagdic, Osman (ELSEVIER, 2022)
Ice creams have big potential to be used as probiotic food carrier. In this respect, this study aimed to produce ice creams with addition of Saccharomyces boulardii and Lactobacillus rhamnosus GG. Probiotic strains were added to the ice cream mixes before and after aging steps of ice cream production and were inoculated as single or mix cultures. Probiotic ice cream products were then characterized and the survival of the probiotic strains were determined during storage period. Both probiotic strains successfully survived during storage period and their numbers were above 6.18 log CFU/g at final date of storage. The rheological parameters of ice cream products improved with the co-inoculation of S. boulardii and L. rhamnosus both before and after aging step. Importantly the aroma profile of ice cream samples altered with probiotic inoculation and ethanol was the major volatile compound in ice cream samples produced with S. boulardii added before aging step. Inoculation of S. boulardii and L. rhamnosus as single cultures also resulted in formation of distinct aroma compounds in ice cream products. The highest overall acceptability score in sensorial evaluation of ice cream products was obtained from the ice cream products produced with inoculation of probiotics after aging step.
Keywords: Ice cream; Probiotic; S; boulardii and L; rhamnosus; Volatile compounds; Aging process; FAT; YOGURT; MILK; Food Science & Technology